PENGARUH TEGANGAN ELEKTROPORASI TERHADAP EFISIENSI TRANSFORMASI PLAMID pND968 BAKTERI ASAM LAKTAT KE E. coli HB101 [The Effect of Electroporation Voltage on Transformation Efficiency of Plasmid pND968 of Lactic Acid Bacteria Into E. coli HB101] - Widodo . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The research was conducted to examine the effect of different electroporation voltage on transformation efficiency of plasmid pND968. This was carried out by exposing the mixture of plasmid pND968 and competent cells of E. coli HB101 on a difference level of electroporation voltage at 1500, 2000 and 2500 Volts. After electroporation, the cells were resuspended in a recovery medium and then poured into ampicilin-containing LB agar. Transformants appeared after 48-72 hours were then recorded. The results showed that electroporation voltage of 2500 Volts with resistance 200 Ohm and capacitor 25 uF resulted in the highest electroporation efficiency at 7.72 x 104 CFU / ug DNA. Transformants confirmation by means of plasmid pND968 isolation showed that all of the ampicillin-resistant transformants harbored the intended pND968 with the expected size.